The Role of School Counselors in Promoting Sustainability in the Post Covid-19 Era to Enhance Child Health and Livelihoods - Iloakasia, Adaobi Jennifer (CV. Literasi Indonesia, 2024)
The most significant challenges for education systems in the post-COVID-19 context have emerged in the areas of child health and sustainable living. This paper aims to investigate the ways through which school counselors contribute to the promotion of sustainability for the benefit of students’ welfare and future. Mental health and environmental problems are becoming intertwined; thus, school counselors play a crucial role in linking sustainability to psychosocial care. The study adopted a descriptive survey design with a sample of 177 participants comprising teachers, students, and members of a selected community. Data gathering was done using a structured questionnaire adapted from Google Forms. The questionnaire used a 4-point Likert scale to capture the level of awareness, implementation, and results of sustainability practices. To increase the validity of the instrument measuring the level of academic stress, the Scale of Academic Stress was reviewed by several experts in educational psychology and counseling. Reliability was determined to have robust validity with a Cronbach’s Alpha coefficient of 0.82, which is the result of the assessment of the stability and reliability of the measurement of the study’s constructs. Descriptive analysis was done in SPSS version 26. Mental health challenges that have been worsened by the pandemic are discussed and the ways that school counselors manage them as they support education that fosters responsible behavior are discussed in the study. Such strategies comprise psychological treatment, personal development education, and coordination with teachers and parents to design a supportive school environment. The research also reveals that due to counselor’s many roles, they can largely contribute to promoting student resilience and a sustainable culture to improve child foolishness and livelihoods.